Hiperrealitas dan Camp dalam Iklan Rokok - Tristan Alfian (DeKaVe, 2019)
An advertisement implies deviation and hidden of certain reality then it leads consumer to hyperreality world. In a context of tobacco advertising, it emphasizes more about image and impression, so consumers are not aware of a risk. The methodology used is qualitative with aesthetics approach and Semiotics. The result shows that tobacco advertising constitutes reality discourse which is hyperreality. It is a discourse about image reality in tobacco advertising which describes, stimulates, and project of a dream world of hyperreality. The imagery in cigarette advertisements cannot be separated from aesthetic creativity that conveys confusion of bookmarks, styles, and challenge of bored is called Camp idiom.